A Study of the Chemical Reactions Leading to Spontaneous Combustion of Pyritic to Black at MT Whaleback, Western Australia - Thornber MR; Davidson LR (The Australasian Institute of Mining and Metallurgy, 1986)
The cause of spontaneous combustion of pyritic black shale has been studied by calorimetry and other techniques. The conditions required for ignition to occur are: 1. A critical mass of pyritic black shale. 2. Acidity. 3. Fine shale particle size. 4. A high ambient temperature. 5. The exclusion of air during the preparation of a calorimeter charge. The reaction is characterised by an initial incubation period during which an unknown phase is produced. The build up and oxidation of this phase results in a chain reaction culminating in ignition. The mechanism is believed to involve the interaction of pyrite, sulphuric acid, ferrous sulphate, or meta-stable oxysulphates, with ammonium nitrate. The recommended strategy for prevention of premature detonation is to neutralise the acids in the shale with quick and slow release alkaline materials.